Islamic Religious Education (PAI) Teachers' Strategies in Instituting Religious Character Values in Students at Muhammadiyah Mororiwawo Vocational School, Soppeng Regency - Musdalifah; Andi Abd. Muis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to find out the strategy of Islamic Religious Education Teachers (PAI) in Instilling the Religious Character of Students at SMK Muhammadiyah Maroriwawo, Soppeng Regency. This research is used as a qualitative type with the consideration that the incident has passed and the data is more in-depth which leads to attitude aspects. There are several strategies for Islamic religious education teachers that can be applied, including exemplary strategies, instilling discipline, habituation and creating a conducive atmosphere. In this case, based on the findings of the research, Islamic Religious Education teachers at SMK Muhammadiyah Marioriwawo Soppeng Regency use habituation strategies, where Islamic Religious Education Teachers at SMK Muhammadiyah Marioriwawo Soppeng Regency more often invite students to get used to practicing something learned, besides that they always supervise students to get used to doing things that are the obligations of students. One of them is to carry out congregational prayers at the Baiturrahman Takalala Grand Mosque at the time of the Dzuhur prayer.